Effects of Supplemental Feeding on Breeding Season Home Ranges and Resource Selection of Northern Bobwhites - Shane D. Wellendorf; William E. Palmer; Allen M. Bostick III (National Quail Symposium Proceedings, 2017)
Providing supplemental food resources for northern bobwhite (Colinus virginanus) has been a common management practice for decades, but its impact on bobwhite home ranges sizes and space use has been debated. Between 2001 and 2007, we established a 397 ha fed study area on Tall Timbers Research Station, which received grain sorghum biweekly along a 19.5 km feed trail. An adjacent 465 ha area was treated as a control with no supplemental food resources. Radio-tagged wild bobwhites were located 3 – 5 times each week throughout the breeding season and we used these locations to calculate home ranges during early breeding season (15 April – 30 June) and late breeding season (1 July – 1 October). We also determined second and third order selection of a 10-m buffer area surrounding the supplemental feed trail using compositional analyses. In total, 552 and 286 bobwhite home ranges were calculated for early and late breeding seasons, respectively. We observed significantly smaller early breeding season home ranges on the fed area (x̄ = 12.3 ha, 95% CL ± 0.6) relative to the control (x̄ = 17.4 ha ± 1.9). Average length of feed trail within home ranges was 583 m and 710 m for early and late breeding season home ranges, respectively. The feed trail buffer area was 3 to 5% of all home ranges. Home range placement was not random with high selection preference for the feed trail buffer area. However, there was a low selection preference for the feed trail buffer area within home ranges. Average distances to the feed trail for bobwhite locations (x̄ = 64.4 m ± 16.1) was similar to random locations (x̄ = 74.4 m ± 16.9). The effect of supplemental feeding on bobwhite home ranges size and resource use was greatest during the early breeding season when food and useable habitat were likely lower in availability. On our study area, supplemental food resources distributed along a feed trail impacted bobwhites during a critical transition period from the spring prescribed burning season to the early breeding season.
Keywords: colinus virginianus; northern bobwhite; Florida; home range; resource selection; supplemental feeding